Distribuição de música na cultura digital: a relação de artistas autônomos com as plataformas de Streaming - Pires, Mateus Macedo (2018)
The basic assumption of this research is that contemporary digital technologies provide differentiated ways of producing, distributing and consuming music today, leading to a reconfiguration of the processes involving productions in the music industry and changes in the ways of enjoying music. Therefore, the main objective of this research is to understand how the relationships of the autonomous artists with the Streaming platforms in the consumption and the distribution of musical productions are given. It seeks to understand how current platforms, particularly Spotify, Deezer and Apple Music (audio distribution), and SoundCloud (social audio network) have changed the monopoly of the music industry, forms of financial collection and relations with the public. It is assumed, to do so, that is necessary to deal with issues that involve the circulation of cultural productions in modernity, through the technologies, communication and social sciences. Walter Benjamin's concept of "loss of aura" and "technical reproducibility", the concept of "mass culture" by Theodor Adorno and Max Horkheimer, the notions involving the networked society of Manuel Castells and the Cyberculture, of Pierre Lévy are important ideas for understanding contemporaneity. Finally, through an analysis of the theoretical perspectives based on these authors of communication and cultural studies, we intend to identify and make explicit the relationship between the technological evolution of the media and the copyrights in music, in order to understand economic, social and cultural practices in contemporaneity regarding musical production